Impacts of pore-throat spaces on movable fluid: Implications for understanding the tight oil exploitation process. (March 2022) - Qu, Yiqian; Sun, Wei; Wu, Hanning; Huang, Shengjun; Li, Teng; Ren, Dazhong; Chen, Bin
Abstract: In this study, a series of experiments were carried out on tight sandstone samples from the Yangchang Formation in the Ordos Basin, China to investigate their pore-throat spaces and fluid flow capacity, including nuclear magnetic resonance (NMR) test, constant-rate mercury injection (CRMI), pore-casted thin section analysis, scanning electron microscopy (SEM), and X-ray diffraction (XRD). The pore-throat space was divided into two main types based on CRMI and NMR results: the throat-dominant space and the intergranular pore-dominant space, and the volume proportions was calculated. Proportions of different pore-throat spaces do not affect the total reservoir space, and the proportion of the throat-dominant space plays an important role in controlling the complexity of the pore-throat structure. The intergranular pore-dominant space contributes the main permeability, which affects the fluid flow capacity of tight sandstone through the large throats connecting intergranular pores. Fluid flow capacity in the intergranular pore-dominant space is related to the configuration of pores and throats, a higher proportion of the short conduit throats exist means a more homogeneous pore-throat structure, bound water is redistributed on the pore-throat surface to form a thin water film after centrifugation, leading to a higher proportion of movable fluid. The change of throat volume proportion to the total pore-throat volume with pore-throat radius was studied based on CRMI. With the increase of the pore-throat radius, the proportion of the throat volume first decreases in a fluctuating manner and then starts to increase rapidly at a certain radius (rt-p ). The rt-p value is believed to determine the fluid flow capacity of the tight sandstone. This study has certain reference significance for understanding the fluid flow during the exploitation process of tight sandstone. Highlights: The pore-throat space was divided into throat- and intergranular pore-dominant for evaluating movable fluid in reservoir. The short conduit throat configuration type leads to higher movable fluid based on the bound water film model. The higher throat volume proportion corresponds to a homogeneous pore-throat structure, which is favorable for fluid flow.